2018
DOI: 10.3390/antiox7120196
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Subsets in Atherosclerosis and Modification with Exercise in Humans

Abstract: Atherosclerosis is a progressive pathological remodeling of the arteries and one of its hallmarks is the presence of chronic inflammation. Notably, there is an increased proportion and activation state of specific monocyte subsets in systemic blood circulation. Monocyte subsets have distinct contributions to the formation, progression, and destabilization of the atherosclerotic plaque. Strong clinical and epidemiological studies show that regular aerobic exercise mitigates the progression of cardiovascular dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 72 publications
0
24
0
2
Order By: Relevance
“…The anti-inflammatory effects of exercise are becoming better understood at being effective for preventing chronic inflammation. Candidate biomarkers are used to reveal the effects of exercise from a pathological point of view or to develop early prognostic markers [48,49,50,96,97,98,99]. However, further prevention of chronic diseases, improvements in quality of life, and an extension of healthy life expectancy by implementing not only exercise but also dietary supplementation and favorable lifestyle factors are anticipated to become more actively promoted in the future [100,101].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The anti-inflammatory effects of exercise are becoming better understood at being effective for preventing chronic inflammation. Candidate biomarkers are used to reveal the effects of exercise from a pathological point of view or to develop early prognostic markers [48,49,50,96,97,98,99]. However, further prevention of chronic diseases, improvements in quality of life, and an extension of healthy life expectancy by implementing not only exercise but also dietary supplementation and favorable lifestyle factors are anticipated to become more actively promoted in the future [100,101].…”
Section: Discussionmentioning
confidence: 99%
“…A study has shown that approximately 100 min of walking exercise per week for three months in elderly people without prior exercise habits resulted in decreased markers of neutrophil activation and oxidative stress [48]. Apart from the effects on neutrophils, various exercise-induced anti-inflammatory effects on the innate immune system have been uncovered: for example, changes in M1/M2 macrophages in fat tissue due to exercise training [25] or arteriosclerosis and changes in blood monocyte subsets [49]. These studies will potentially expand from preventive medicine to preemptive medicine to reveal the effects of exercise from a pathological mechanism point of view or to develop early prognostic markers.…”
Section: Chronic Inflammation and Anti-inflammatory Effects Of Exementioning
confidence: 99%
See 1 more Smart Citation
“…A feature of atherosclerosis is chronic inflammation and increased activation of monocytes in the systemic blood circulation. Monocytes are cells with a myeloid origin, which are actively engaged in systemic and chronic inflammation and have distinct contributions to the formation, progression, and destabilization of the atherosclerotic plaque [15]. The metabolism of monocytes can be reprogrammed in the atherogenic microenvironments, which consist of hypoxia, molecular damage, and modified lipoproteins [16].…”
Section: Introductionmentioning
confidence: 99%
“…These reviews are complimented by overviews of the influences of specific and more general dietary factors, such as β-hydroxy-β-methylbutyrate (HMB) by Arazi and colleagues [16], and antioxidant intake by Kawamura and Muraoka [17]. Finally, perspectives relating to the pathophysiological conditions of atherosclerosis [18] and heat stroke [19] are provided. Empirical studies include an in vitro model of muscle cell damage [20], the investigation of nutrient supplementation such as alpha-lipoic acid [21], HMB [16], barley-wheat grass juice [22] and graded carbohydrate intake [23], and an investigation into the efficacy of post-exercise hydrogen baths [24].…”
mentioning
confidence: 99%